(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The study of vitamin D-dependent risk factors for the formation of essential arterial hypertension (EAH) based on the assessment of serum levels of calcidiol (25 (OH) D), calcium, and vasoconstrictor factor endothelin-1-21 in 132 students aged 13 to 16 years (average age 14.64 ± 0.19 years) with normal, high normal blood pressure and essential arterial hypertension (EAH) established the priority effect of vitamin D supply on the level of diastolic blood pressure in the group of children with labile arterial hypertension and in the group of children with stable parameters of systolic blood pressure. In the mechanism of EAH formation in children, an interdependence between vitamin D deficiency and the severity of endothelial dysfunction by the level of endothelin-1-21 was revealed. The following vitamin D levels were determined by diagnostic efficiency-dependent risk factors for the formation of EAH in children in decreasing importance: endothelin-1-21> 0.41 fmol/mL; vitamin D < 20 ng/mL; Ca < 2.22 mmol/L.